Gender Domesticity Reinterpreted: Housework Division in Dual-Work Moroccan Families - Meryem, Rostom (European Scientific Journal, ESJ, 2018)
Research on the gendered division of household labour suggests that spouses’ inequitable housework division is determined by economic, cultural and/ or pragmatic considerations. While these factors are partially supported by the literature on household labour division, results of this study further suggested that women perform more housework than their spouses out of choice and are not necessarily unhappy with their unbalanced share. The data for the study were drawn from in-depth semi-structured interviews administered to 30 Moroccan female primary school teachers. Building on Thompson’s (1991) distributive justice framework, this paper focuses on examining women’s underlying motivation for doing a far greater proportion of housework tasks than do their husbands in spite of working for pay. It also states the implications of such a deliberate choice.